Regular AREDS2 Supplement Use in Age-Related Macular Degeneration: Factors Associated with Supplementation, Medication Adherence, and Patient-Reported Barriers - Hasan Öncül; Umut Dağ; Mehmet Fuat Alakuş (Healthcare, 2026)
Background/Objectives: Age-related macular degeneration (AMD) is a leading cause of irreversible visual impairment, and AREDS2-based nutritional supplementation is recommended for clinically eligible patients to reduce the risk of disease progression. However, successful implementation depends on regular supplement use and sustained adherence. This study investigated demographic, socioeconomic, clinical, and physician-related factors associated with regular AREDS2 supplement use and evaluated medication adherence, physician counseling, and patient-reported barriers among clinically eligible patients with AMD. Methods: In this single-center cross-sectional study, 389 patients with intermediate AMD or advanced AMD in one eye who fulfilled the indications for AREDS2 supplementation were enrolled. Participants reporting occasional supplement use were excluded. A structured interviewer-administered questionnaire was used to collect demographic, socioeconomic, and clinical data, together with information on physician recommendation, medication adherence, patient knowledge, and perceived barriers to supplementation. Factors associated with regular AREDS2 supplement use were evaluated using univariable and multivariable logistic regression analyses, whereas adherence patterns and patient-reported barriers were analyzed descriptively. Results: Of the 389 participants, 273 (70.2%) reported regular AREDS2 supplement use, whereas 116 (29.8%) were non-users. Multivariable analysis showed that younger age, educational attainment, and physician recommendation were independently associated with regular supplement use (adjusted OR for physician recommendation, 5.38; 95% CI, 2.68–10.81; p < 0.001). Among regular users, 53.5% met the study-defined criteria for good medication adherence. The most frequently reported barriers among non-users were financial burden, limited supplement availability, polypharmacy, and insufficient knowledge regarding AREDS2 supplementation. Conclusions: Regular AREDS2 supplement use among clinically eligible patients with AMD was associated with demographic, educational, and physician-related factors, whereas long-term adherence remained suboptimal despite substantial uptake. These findings emphasize the importance of effective physician counseling, structured patient education, and interventions addressing socioeconomic barriers to improve the real-world implementation of evidence-based nutritional supplementation in AMD.